Higher education reform and the landscape diversity of higher education institutions in the Kyrgyz Republic, 1991–2015 - Shadymanova, Jarkyn; Amsler, Sarah (Palgrave Macmillan, 2018)
Following its independence from the Soviet Union in 1991, Kyrgyzstan experienced processes of change across all areas of social, political and economic life. Higher education reform has been central to this agenda, and between 1991 and today the Soviet-era system of state-funded and Communist Party controlled higher education institutions (HEIs) in Kyrgyzstan has been transformed into an expansive, diverse, unequal, semi-privatized and marketized higher education (HE) landscape. Mindful of arguments that the marketization of higher education does not necessarily generate institutional diversification, that government regulation does not necessarily lead to homogenization among institutions, and that universities’ own institutional strategies and responses to environmental changes shape processes of structural reform in complex ways, this paper assesses the specific character of these changes to the higher education landscape in post-Soviet Kyrgyzstan. After briefly describing the structure and financing of higher education in the Kirgiz Soviet Socialist Republic from 1917–1991, we consider some key factors which have shaped patterns of the differentiation and diversification of HE in the post-Soviet period. These include the historical legacies of Soviet HE infrastructures, new legal and political frameworks for HE governance and finance, changes to regulations for the licensing of institutions and academic credentials, the introduction of new multinational policy agendas for higher education in the Central Asian region, changes in the relationship between higher education and labor, the introduction of a national university admissions examination, and the adoption of certain principles of the European Bologna Process. The picture of HE reform that emerges from this analysis is one in which concurrent processes of diversification and homogenization are not driven wholly by either state regulation or forces of market competition, but mediated by universities’ strategic negotiations of these forces in the context of historical institutional formations in Kyrgyzstan.